2011
DOI: 10.1038/bmt.2011.77
|View full text |Cite
|
Sign up to set email alerts
|

Oral epithelial dysplasia and squamous cell carcinoma following allogeneic hematopoietic stem cell transplantation: clinical presentation and treatment outcomes

Abstract: Background Late complications of allogeneic hematopoietic stem cell transplantation (HSCT) include a risk of secondary malignancies, including oral cancers. Optimization of best clinical practices for early diagnosis and treatment of oral premalignant or malignant lesions requires an assessment of potential predisposing risk factors as well as treatment outcomes. Methods The medical records of patients who developed oral epithelial dysplasia (OED) and oral squamous cell carcinoma (OSCC) following allogeneic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(83 citation statements)
references
References 57 publications
(53 reference statements)
2
77
0
Order By: Relevance
“…In contrast, a study of 354 cases of OSCC found that ulcers were the most frequent presentation (48.5%), followed by exophytic growths . In OSCC arising following allogeneic bone marrow transplantation, the most frequent clinical features at diagnosis were plaques (50%), exophytic masses (39%), and ulcers (28%); however, there may be unique features to this particular background of immunosuppression .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a study of 354 cases of OSCC found that ulcers were the most frequent presentation (48.5%), followed by exophytic growths . In OSCC arising following allogeneic bone marrow transplantation, the most frequent clinical features at diagnosis were plaques (50%), exophytic masses (39%), and ulcers (28%); however, there may be unique features to this particular background of immunosuppression .…”
Section: Discussionmentioning
confidence: 99%
“…While mucoepidermoid carcinoma of the parotid gland and oral carcinomas are uncommon in childhood, they develop at increased rates in survivors of childhood cancer, particularly after radiotherapy and HSCT [8688]. Squamous cell carcinoma accounts for approximately one-third of solid SMNs after HSCT, with 50 % occurring in the oral cavity [89]. The CCSS reported childhood cancer survivors had a significantly higher risk of head and neck carcinoma compared to the general population (standardized incidence ratio [SIR] 13.6 [8.9–20.9]) with a prevalence of 0.2 % [87].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, survivors with cGVHD are at an increased risk for developing oral SMNs [85, 90]. Oral cGVHD was present in 23 of 26 individuals aged 14 to 67 years with oral epithelial dysplasia or squamous cell carcinoma following HSCT [89]. Host risk factors associated with an increased risk of oral cancer include younger age at HSCT and underlying cancer predisposition syndromes, such as Fanconi anemia and dyskeratosis congenita [85, 87, 88, 92, 93].…”
Section: Resultsmentioning
confidence: 99%
“…Minimal data exist on treatment outcomes, but it appears that these secondary oral cancers may be associated with higher rates of recurrence and poorer long-term survival compared with de novo squamous cell carcinoma of the oral cancer in non-HCT patients. 29 In conclusion, oral cGVHD is a frequent and potentially serious complication after allogeneic HCT. Although not inherently lifethreatening, it is associated with significant morbidity because of pain and dysfunction, restricted oral intake, and secondary complications.…”
Section: Squamous Cell Carcinomamentioning
confidence: 99%
“…25 Patients with oral cGVHD are at a significantly increased risk for developing oral squamous cell carcinoma, which can present with a wide array of clinical features, including ulceration, induration, and exophytic and endophytic growth patterns ( Figure 12). [26][27][28][29] These lesions may be difficult to discern from mucosal cGVHD changes; thus, referral to a specialist for biopsy is essential for timely and appropriate therapy.…”
Section: Other Associated Conditionsmentioning
confidence: 99%